ANALISIS KEPUTUSAN PEMBELIAN HANDPHONE XIAOMI - Muhammad Rizki Saputra (2020)
This research takes the form of quantitative research that aims to explain the impact of brand equity, price, and quality of products on purchasing decisions. This study took a sample of Xiaomi mobile users. Samples taken were a number of 75 respondents, with a sampling technique using probability sampling and using simple random sampling. Data collection is obtained through the distribution of questionnaires conducted virtually without face to face by utilizing technology in the network (online). Smart PLS 3.0 software is used by researchers to analyze data using the PLS (Partial Least Squares) method. The final results obtained by researchers show how on one side of the variables of brand equity and product quality can influence a purchasing decision by consumers with a significant number. Meanwhile on the other hand the price variable has an ineffective and significant influence on purchasing decisions of Xiaomi phones..